Values Of Life In The Wild Duck By Hendrik Ibsen - Gusti Ayu Made Rai Suarniti (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
This study aims to analyze and discuss the values in Hendrik Ibsen’s The Wild Duck. The method used in this study is descriptive. The data are a drama entitled The Wild Duck (1959). A library research method is applied in collecting the data. Furthermore, the data is analyzed qualitatively. Based on the result of the analysis, it was revealed that there are five kinds of Values found in The Wild Duck which are Moral Value, Social Value, Personal Value, Spiritual Value and Family Value. The most presented type is a moral value, it is about honesty. Social value is about interaction with around, friendship, respect to each other, justice. A personal value is a personality. Spiritual is non-material, it means the values of truth, inner peace, righteousness, and non-violence and the last is family values are beliefs, function as a family, ideals.